Defining a Distinct Immunotherapy Eligible Subset of Patients with Cancer of Unknown Primary Using Gene Expression Profiling with the 92‐Gene Assay. (23rd September 2020) - Raghav, Kanwal; Overman, Michael; Poage, Graham M.; Soifer, Harris S.; Schnabel, Catherine A.; Varadhachary, Gauri R.
Abstract: Background: Although recent advances in immunotherapy have transformed the treatment landscape for many anatomically defined cancers, these therapies are currently not approved for patients diagnosed with cancer of unknown primary (CUP). Molecular cancer classification using gene expression profiling (GEP) assays has the potential to identify tumor type and putative primary cancers and thereby may allow consideration of immune checkpoint inhibitor (ICI) therapy options for a subset of patients with CUP. Herein, we evaluated and characterized the ability of a 92‐gene assay (CancerTYPE ID) to provide a molecular diagnosis and identify putative tumor types that are known to be sensitive to ICI therapies in patients with CUP or uncertain diagnosis. Findings: A total of 24, 426 cases from a large‐scale research database of 92‐gene assay clinical cases were classified, of which 9, 350 (38%) were predicted to have an ICI‐eligible tumor type. All ICIs with approved indications as of March 2020 were included in the analysis. Non‐small cell lung cancer (NSCLC) was the most frequent molecular diagnosis and accounted for 33% of the ICI‐eligible tumor types identified and 13% of the overall reportable results. In addition to NSCLC, the assay also frequently identified urothelial carcinomas, gastric cancer, and head and neck squamous cell carcinoma. The distributions of identified tumor types with indications for ICI therapy were similar across age and gender. Conclusions: Results suggest that molecular profiling with the 92‐gene assay identifies a subset of ICI‐eligible putative primary cancers in patients with CUP. We propose a treatment strategy based on available tests, including clinicopathologic features, GEP, and ICI biomarkers of response. Abstract : Regulatory approval of immune checkpoint inhibitors (ICI) is restricted to anatomically defined cancers with a known primary. This article reports cases submitted for 92‐gene assay testing with an unknown or uncertain diagnosis for which the subsequent post‐test report included a tumor type linked to an FDA‐approved ICI therapy, with the goal of identifying characteristics of cancers of unknown primary tumors that might benefit from immunotherapy.